Ganglion Cell and Retinal Nerve Fiver Layers Correlated with Time Disease of Bipolar Disorder Using 64 Cell Grid OCT Tool. (3rd August 2021) - Orduna-Hospital, Elvira; Cordón, Beatriz; Vilades, Elisa; Garcia-Martin, Elena; Garcia-Campayo, Javier; López-Del-Hoyo, Yolanda; Polo, Vicente; Larrosa, Jose M.; Pablo, Luis E.; Satue, Maria
ABSTRACT: Purpose of the study : To assess the ability of the new Spectralis Optical Coherence Tomography (OCT) Posterior Pole protocol to detect degeneration of the inner retinal layers in patients with bipolar disorder (BD) and to assess the correlation between the neuroretinal thickness and disease duration. Materials and Methods: Twenty-five eyes of 25 patients with bipolar disorder and 74 eyes of 74 healthy controls underwent retinal measurements of retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) thickness. Measurements were obtained using the Spectralis-OCT device with the new Posterior Pole protocol which assesses the macular area by analyzing retinal thickness in a grid of 64 (8*8) cells. Results: Significant differences ( p < 0.05) in RNFL and GCL thickness were found between BD patients and healthy controls, in parafoveal and perifoveal cells respectively. Significant inverse correlations were found between RNFL and GCL thinning at their thickest location and the duration of bipolar disorder. Several predictive variables were observed with a binary logistic regression for the presence/absence of BD: cell 1.3 RNFL ( p = 0.028) and GCL in cells 7.8 ( p = 0.012), 2.7 ( p = 0.043) and 1.3 ( p = 0.047). Conclusion: Posterior Pole OCT protocol is a useful tool to assess changes in the inner retinal layers in bipolar disorder. These observed changes, especially those affecting the GCL, may be associated with disease evolution and may be predictive of the presence of the disease. OCT data could potentially be a useful tool for clinicians to diagnose and monitor BD patients.